IMPACT OF DIGITAL TRANSFORMATION, ELECTRONIC SERVICES AND AI TECHNOLOGIES ON MANAGEMENT EFFICIENCY IN SERVICE ENTERPRISES (Marketing Journal, 2025)
This article provides a theoretical and empirical analysis of the impact of digital transformation, electronic services and artificial intelligence technologies on the management efficiency of service enterprises. The study examines the digital development dynamics of the service sector in Uzbekistan and worldwide, the role of AI in process optimization, and the effects of electronic services on service quality and customer satisfaction. The results indicate that service delivery speed increased 3.5 times, operational costs decreased by 18%, and customer satisfaction rose by 19%. Furthermore, AI -CRM, chatbots, and predictive analytics demonstrated a strong positive impact on managerial efficiency. 399
Keywords: digital transformation; electronic services; AI technologies; service sector; management efficiency; digital economy